The Survival Rate and Starch Histochemical Assay of Various Stem Cutting Conditions of Mentega 2 Cassava Genotype at Initial Growth Stage - Sri Hartati; Hani Fitriani; Nanang Taryana; Nawawi Nawawi; Yani Cahyani; Siti Kurniawati; Enny Sudarmonowati (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Background: This study aimed to evaluate the growth ability of cassava mini stem cuttings with different node number and a variety of stem cutting shapes and their correlation with starch content in the stems at initial growth stages. Methods. In this study, the viability of cassava stem cuttings was identified in two type experiments i.e. mini-stem cuttings consisting 1 and 2 nodes and shape variation of single node mini-stem cutting. Parameters observed were shoots emergence period, number of sprouting cuttings, shoots number of individual stem cuttings, shoots height and number of leaves. In addition, starch histochemical test was also carried out on stems of young shoots and initial stem cuttings using Lugol's solution. Results. Both cassava stem cuttings consisting of 1 and 2 buds indicated the same survival rate of 100%. 1 bud stem cuttings with different shapes showed different survival rate, i.e. 60-80% for semicircular and fully circular cuttings and 30-40% for box shape cuttings. The difference in survival rate with different stem size is probably related to the availability of the amount of starch to support shoots growth. Observations at week 3 after planting generally showed that the stem cuttings with 2 buds were higher than those of stem with 1 bud. Conclusion: There were differences in the scores on the starch content test qualitatively with Lugol staining, in various parts of the plant originating from 1 bud and 2 bud cuttings which may indicate a breakdown of starch during shoot development.